1999
DOI: 10.1046/j.1570-7458.1999.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of avocadofurans on larval survival, growth, and food preference of the generalist herbivore, Spodoptera exigua

Abstract: We examined the effect of two avocadofurans, 2‐(pentadecyl)furan and 2‐(heptadecyl)furan, from avocado idioblast oil cells on maturation and larval feeding behavior of a generalist insect herbivore, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae). Experiments were conducted using two larval sizes: early‐stadium larvae refer to those larvae from experiments initiated with neonates while late‐stadium larvae refer to those larvae from experiments initiated with third instars. In order to use selected subletha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The 2‐[(8 Z ,11 Z )‐heptadeca‐8,11‐dienyl]furan reduces larval growth of B. mori . The avocadofurans have insecticide and feeding deterrent activity against non‐adapted herbivorous insects such as S. exigua . Squalene is reported as attractant for parasitoids and predators of apple insect pests .…”
Section: Resultsmentioning
confidence: 99%
“…The 2‐[(8 Z ,11 Z )‐heptadeca‐8,11‐dienyl]furan reduces larval growth of B. mori . The avocadofurans have insecticide and feeding deterrent activity against non‐adapted herbivorous insects such as S. exigua . Squalene is reported as attractant for parasitoids and predators of apple insect pests .…”
Section: Resultsmentioning
confidence: 99%
“…While plant metabolites may produce toxic eVects when ingested by insects, antifeeding activity may determine the extent of insect herbivory. Several papers have been published on the entomotoxic properties of crude extracts from diVerent plant species (Sadek 1997(Sadek , 2003Rodriguez-Saona and Trumble 1999;Ciccia et al 2000;Tapondjou et al 2005). However, utilization of many phytochemicals as botanical insecticides and/or antifeedants is still at an early stage of development.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies identified various compounds in the avocado idioblast oil, including persin and several alkylfurans, which are responsible for the toxicity and antifeedant effects observed for S. exigua (Rodriguez-Saona et al, 1997, 1998Rodriguez-Saona & Trumble, 1999). In this study, we provide the first experimental evidence that idioblast oil cells can serve a defensive function in deterring non-adapted herbivores.…”
Section: Discussionmentioning
confidence: 69%
“…However, Kobiler et al (1993) also indicated that intact idioblast cells in the fruit mesocarp were not toxic to C. gloeosporioides, and proposed that the cell thickness blocks contact with fungal hyphae. The 2-alkylfurans were reported to cause toxic (Rodriguez-Saona et al, 1998) and feeding deterrent effects (Rodriguez-Saona & Trumble, 1999) on the non-adapted S. exigua larvae. Similarly, oil extracted from idioblast cells was toxic to the beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) (Rodriguez-Saona & Trumble, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation